The Growth and Development of Belgrade in the Period from 1815 to 1910 - Vukotić Lazar, Marta M.; Danilović Hristić, Nataša M. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
Belgrade has been devastated and redeveloped for countless times. Various cultures, nations and conquerors left different urban matrices and physical structure. The groundwork for conceptualization and research of the urban matrix as an essential element of Belgrade’s urban morphology are graphic presentations - the old maps and plans. Appreciating strategic significance Belgrade had up till 19th century, they were mainly elaborating Belgrade Fortress area, while civil settlement – the Borough inside the Trench, a small typically oriental town was presented in general sketches. This paper deals with breakthrough conceptions about planned construction of Belgrade inside and outside of the fortress moat from the beginning of the 19th till the beginning of the 20th century. The ruling period of Prince Miloš Obrenović was especially emphasized, when planned construction of the new, geometrically regulated Belgrade settlement in Western Vračar (outside the Trench) started and was supposed to be connected with the city center of the Serbian Belgrade (inside the Trench) around the current Saborna church, via two already existing streets – Abadžijska Street and Fišeklijska Street. Prince Miloš in 1815., obtained from Marašli Ali Pasha the Savamala area with the formed village on so called slope, that was soon to be destroyed and set on fire upon his order, with the goal of building “a new Serbian Belgrade”. The expelled landowners gained the opportunity to settle down on the Danube side, in the village of Palilula. In the third and the fourth decade of the 19th century there started the planned guidance of population of respective urban areas and regulation of some tracings in Savamala and Terazije as far as the Batal Mosque, forming on the slopes of Savamala and Western Vračar a new part of Serbian Belgrade, beyond the Trench with several new “čaršija’’.In the period 1835-38, Prince Miloš began developing some prominent edifices and institutions of the restored Province of Serbia in this Belgrade area, and his son, Prince Mihailo Obrenović, continued with the development of this area after 1860
Keywords: morphology; history; architecture; urban heritage